TOWARDS SOCIAL ENTERPRISE SUSTAINABILITY: A CASE STUDY OF SOCIAL ENTERPRISE IN INDONESIA - FARHANA, ADINDA (LPPM UNIVERSITAS INSAN PEMBANGUNAN INDONESIA, 2026)
Social Enterprises (SEs) often emerges as an actor who tackle social problem that government failed to address. Especially in Indonesia, where it is challenging to reach disadvantages people across the archipelago. Despite the crucial presence of SEs, it often encountered many challenges that hamper the way towards sustainability. In response to this, there are many factors that influence SEs sustainability. Hence, this study aims to seek the meaning of Sustainability from the lens of Social Enterprise and gain insight of factors influence SEs sustainability. Qualitative multiple case study methodology was conducted to interpret the data. Seven social enterprises from three different sector namely agriculture & fisheries, creative industry, and education was selected to answer the phenomenon under study. Secondary data collection obtained from academic papers, article, videos, and SEs report was conducted to enrich the study findings. This study proposed conceptual framework of factors that influence SEs sustainability. Finally, this study provides theoretical and managerial implication that can be considered by all stakeholders in SEs ecosystem.